Strengthening the Professional Writing Competence of MGMP French Teachers at SMAN 19 Medan with Fiche de Travail Numérique - Mahriyuni; Tengku Syarfina; Deliana; Erikson Saragih (English Lecturers and Teachers Association (ELTA), 2024)
This program aimed to improve the professional writing competence of MGMP French teachers at SMAN 19 Medan, who face challenges such as errors in tenses, sentence structure, prepositions, and gender agreement in French writing. These difficulties hinder their ability to teach effectively and meet established competency standards. To address this, the program utilizes fiche de travail numérique from the Allez-Écrire website, offering interactive digital worksheets designed to enhance writing skills. The approach includes situation analysis, problem identification, material development, mentoring, and evaluation. Teachers' weaknesses were identified through observations and interviews, followed by implementing fiche de travail numérique with automatic feedback exercises. Evaluations were conducted to measure improvements before and after the program. The results show a significant increase in writing competence: errors in passé composé and imparfait usage decreased by 45%, sentence structure and conjunction errors by 40%, and gender agreement errors by 40%. These findings indicate that digital worksheets are effective in helping teachers correct mistakes, boost confidence, and produce better writing. The program is proven to enhance French writing competence and is recommended to be expanded with more interactive materials and ongoing support for continuous improvement Keywords : Professional competence; Writing; French; Fiche de Travail Numérique; MGMP